Perceived influence of self-perception on self-esteem among undergraduate students of Kabarak University in Nakuru County, Kenya - Kiptiony, Gladys; Murgor, Nelly Jebet; Kay, James (Journal of Psychology and Behavioural Sciences, 2024)
The purpose of this study was to determine perceived influence of selfperception on self-esteem among undergraduate students of Kabarak University, Kenya. The objective of the study was to establish the perceived influence of self-perception on self-esteem among undergraduate students of Kabarak University. The study involved 3rd year undergraduate students, two university counsellors and ten peer counsellors as respondents. Questionnaire was used for undergraduate students, FGD guide for peer counsellors and interview schedule for university counsellors. Reliability and validity of items was established using Cronbach Alpha Coefficient. The results of the variable self-esteem yielded 0.705, while body image yielded 0.937. The response rate was 96.39 per cent. The collected data was analysed using percentages, frequencies and means (descriptive statistics) using Statistical Package for Social Sciences (SPSS). The results indicated that the majority of the sampled students and staff jointly agreed that selfperception influences self-esteem among undergraduate students of Kabarak University. The study concluded that self-perception has a statistically significant perceived influence on self-esteem among undergraduate students of Kabarak University. Therefore, the study recommends that key stakeholders in counselling department include in the policies and strategies ways on how to address concerns about selfperception and self-esteem. The research data serves to strengthen efforts by university policymakers and management bodies to enhance the counselling departments by coming up with policies and strategies The study recommends increasing awareness of self-perception, helping students appreciate their bodies, feel comfortable in their own skin, and know that there is more to their worth than just physical appearance.
Keywords: Influence, self-esteem, self-perception, third years, undergraduate students